Elliptic Differential-Difference Equations with Incommensurable Shifts of Arguments - Ivanova, Elena Pavlovna (Eurasian Mathematical Journal, 2016)
This article deals with the problem of strong ellipticity of differential-difference equations with incommensurable argument’s shifts.